PENDAMPINGAN MANAJEMEN PASCAPANEN GUNA MENINGKATKAN PENDAPATAN KELOMPOK WANITA TANI PADI DI DESA SUREN JEMBER - Iqbal Erdiansyah; Berlina Yudha Pratiwi; Christa Dyah Utami; Eliyatiningsih Eliyatiningsih; Rindha Rentina Darah Pertami; Fitriyatul Hanifiyah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
Post-harvest handling of paddy is very important effort to support increasing national rice production. So far, the main problem faced in post-harvest handling of rice is the high rate of yield loss due to incorrect post-harvest activities. KWT Jaya Mulia is one of the groups that carries out post-harvest rice activities in Suren Village, Ledokombo District, Jember Regency. In carrying out its activities, KWT Jaya Mulia is still hampered by limited knowledge and skills in carrying out post-harvest handling. This community service activity aims to increase the knowledge and skills of KWT in carrying out post-harvest rice activities. Activities carried out include knowledge dissemination, skills training, mentoring, and evaluation activities. Based on the evaluation of activities that have been carried out, it is known that there has been an increase in the knowledge and skills of KWT in carrying out post-harvest rice activities, which include drying grain, packaging and storing it in the storage warehouse properly according to procedures. It is hoped that from this activity, KWT can increase their income Keywords: rice, paddy, post-harvest, income